Cognitive levels towards performance of mathematics score in secondary school / Ilya Zulaikha Zulkifli, Nor Faezah Mohamad Razi and Nor Hazlina Mohammad - Zulkifli, Ilya Zulaikha; Mohamad Razi, Nor Faezah; Mohammad, Nor Hazlina (Universiti Teknologi MARA, Perak, 2021)
Cognitive is relating to cognition. It refers to the method by which knowledge is acquired and manipulated. Usually, cognition is mental. The mental processes associated with phenomena such as concentration, logic, thought and evocation. Generally, characterized as reflects the mind. It is not observable directly, but it must be inferred. Malaysian educators trying so hard to make sure all students master or at least having good knowledge in Mathematics. Investigation on cognitive levels towards performance of Mathematics score among secondary school's students is the main purpose of the study. A secondary data was used for the process of investigation. A total of 118 secondary school's students in Tapah were involved randomly. The analyses were started using multiple linear regression with the aid of IBM SPSS version 24. Results show that cognitive levels significantly affect the performance of Mathematics score. These cognitive levels include Knowledge (C1), Comprehension (C2), Proficient (C3), Synthesis (C5), and Analysis (C6). Among five levels of cognitive, results show that Comprehension (C2) or in other words understanding of facts and ideas give the highest impact towards the performance of Mathematics score. If the students do not understand well in topics covered from Mathematics, they will not perform well in Mathematics. In this situation, both teachers and students play an important role to make better results in Mathematics.